Representation of Mother Castrator In The Short Story of Perempuan Buta Tanpa Ibu Jari by Intan Paramaditha - Henry Reggy Leo Capital; S Sulistyaningsih (Jurnal Langua, 2023)
Patriarchy is always cited as the main cause of gender injustice such as women’s oppression, violence, gender, existence, and a lot more. Females oftentimes are victims of male dominance, however, females can also be dreadful figures, it is called monstrous feminine. Mother castrator is one of the monstrous feminine part, it is showing a mother with obsession and a dominant character that destroys her children and it can be found in the short story of Perempuan Buta Tanpa Ibu Jari by Intan Paramaditha. The purpose of this study is to describe a representation of mother castrator in the story of Perempuan Buta Tanpa Ibu Jari. This research is descriptive qualitative research and the researcher finds that mother castrator is represented in the story. It can be seen from the presence of a knife, mutilated body parts, and women’s futures that are robbed. Mother castrator is a form of power and obsession of a mother to her children, and it is misused. As the result, it victimizes her children’s physic and future.feminism, monstrous feminine, mother castrator